The features of the internal picture of the disease in patients with diabetes mellitus type 2, depending on the duration of the disease - Kachan, Elena P.; Kulak, Alexandra I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Authors describe characteristics of the internal picture of the disease (IPD). Value of research of IPD in clinic of somatic diseases is proved. The chosen methodology and methods of research is reasoned. Within the IPD multilevel theoretical model (V. V. Nikolaeva) features of an internal picture of an disease on each of the considered levels (sensual, emotional, intellectual and motivational) at patients with diabetes of the type 2 depending on disease duration come to light. According to results of research the most adaptive period of a course of disease at patients with diabetes of the type 2 is determined.